Isotropic porous structure design methods based on triply periodic minimal surfaces - Jiawei Feng; Bo Liu; Zhiwei Lin; Jianzhong Fu (Materials & Design, 2021)
Recently, triply periodic minimal surface (TPMS) is emerging as an ideal tool to generate porous structures. Yet, most of the current work only focuses on controlling the elastic modulus by the relative density. For special engineering applications, such as porous bone implants or energy absorbers, the generated porous TPMS may still be broken due to anisotropy. In this work, two strategies are proposed to design isotropic TPMS structures. The numerical homogenization theory and finite element analysis methods are utilized to study the relationship between TPMS parameters and the elastic modulus or anisotropy properties. Based on that, a Curvature-Wall thickness (CW) adjustment method is proposed for sheet TPMS structures whose performances are close to isotropy properties. In virtue of the constructed design map, both elastic modulus and anisotropy properties can be controlled. For sheet TPMS structures whose performances are far from the isotropy properties, the TPMS units can be combined to generate composite TPMS, which can be further designed by the proposed Curvature-Wall thickness adjustment method. Experimental results verify the effectiveness and accuracy of the proposed approaches. Appropriate elastic modulus and ideal isotropy properties can be acquired at the same time.